Cyanoacetylene in the outflow/hot molecular core G331.512−0.103. Issue 2 (31st July 2019) - Duronea, N U; Bronfman, L; Mendoza, E; Merello, M; Finger, R; Reyes, N; Hervías-Caimapo, C; Faure, A; Cappa, C E; Arnal, E M; Lépine, J R D; Kleiner, I; et al.
ABSTRACT: Using APEX-1 and APEX-2 observations, we have detected and studied the rotational lines of the HC3 N molecule (cyanoacetylene) in the powerful outflow/hot molecular core G331.512−0.103. We identified 31 rotational lines at J levels between 24 and 39; 17 of them in the ground vibrational state v = 0 (9 lines corresponding to the main C isotopologue and 8 lines corresponding to the 13 C isotopologues), and 14 in the lowest vibrationally excited state v 7 = 1. Using local thermodynamic equilibrium (LTE)-based population diagrams for the beam-diluted v = 0 transitions, we determined T exc = 85 ± 4 K and N (HC3 N) = (6.9 ± 0.8) × 10 14 cm −2, while for the beam-diluted v 7 = 1 transitions we obtained T exc = 89 ± 10 K and N (HC3 N) = (2 ± 1) × 10 15 cm −2 . Non-LTE calculations using H2 collision rates indicate that the HC3 N emission is in good agreement with LTE-based results. From the non-LTE method, we estimated T kin ≃90 K, n (H2 ) ≃ 2 × 10 7 cm −3 for a central core of 6 arcsec in size. A vibrational temperature in the range from 130 to 145 K was also determined, values which are very likely lower limits. Our results suggest that rotational transitions are thermalized, while infrared radiative pumping processes are probably more efficient than collisions in exciting the molecule to the vibrationally excited state v 7 = 1. Abundance ratios derived under LTE conditions for the 13 C isotopologues suggest that the main formation pathway of HC3 N is C2 H2 + CN → HC3 N + H.